1995
DOI: 10.1006/viro.1995.9949
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Sites on the Receptor-Binding Domain of Human Adenovirus Type 2 Fiber

Abstract: The trimeric fiber of adenovirus type 2 (Ad2) mediates the first stage of virus-cell attachment, and the distal head region of the fiber has been implicated as the receptor-binding domain. To locate regions on the primary polypeptide sequence of the fiber which may be involved in virus-cell interaction, peptide-based epitope mapping was performed using (1) polyclonal antibodies prepared against both native Ad2 fiber and Ad2 head protein expressed in Escherichia coli and (2) 18 monoclonal antibodies prepared ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 4 publications
3
32
0
Order By: Relevance
“…However, significant differences between adenovirus viability (N/N 0 ) and fiber protein integrity (F/F 0 ) were observed at each pH (Table 3). These results indicate that the region of the fiber knob responsible for binding to the antifiber antibody, which is critical for binding CAR (6), is relatively stable during free chlorine exposures that result in adenovirus inactivation.…”
Section: Vol 76 2010 Mechanistic Aspects Of Ad2 Inactivation By Frementioning
confidence: 85%
“…However, significant differences between adenovirus viability (N/N 0 ) and fiber protein integrity (F/F 0 ) were observed at each pH (Table 3). These results indicate that the region of the fiber knob responsible for binding to the antifiber antibody, which is critical for binding CAR (6), is relatively stable during free chlorine exposures that result in adenovirus inactivation.…”
Section: Vol 76 2010 Mechanistic Aspects Of Ad2 Inactivation By Frementioning
confidence: 85%
“…Using several approaches, it has been shown convincingly that hexon is the major target for neutralization (8,14,28,34,45). Antifiber and anti-penton base NAbs that block primary receptor interactions and integrin-mediated internalization, respectively, have been identified (7,13,19,32,45); however, they likely represent only a small portion of the neutralizing activity of serum. Studies of the mechanisms of antiHAdV NAbs have identified modes of action that are common to antibody neutralization of other viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralizing antibody responses to adenoviruses are directed against components of the virion surface, primarily against fiber, penton base, and hexon (35). Neutralizing antibodies against fiber are qualified to block binding of the fiber knob to its cellular attachment receptor and to aggregate virions by cross-linking fibers on separate virus particles (14). Neutralizing antibodies against penton bases are mainly directed against the integrin-binding RGD motif and prevent virus internalization (18).…”
Section: Discussionmentioning
confidence: 99%